An estimate of burnout prevalence among oncology nurses - Madeleine Helaß; Imad Maatouk (BMC, 2024)
Abstract Background Registered nurses (RNs) in oncology must cope with the suffering of patients, the inevitability of death and their own transience. This poses a possible risk for the development of burnout, which can result in low job satisfaction and ultimately an increased intention to leave the job. Our aim was to assess psychological distress in registered nurses working in oncology. Objective and method A cross-sectional survey with the Oldenburger Burnout Inventory was presented to nurses within the German Cancer Society. It collected data on psychological distress via two subscales, exhaustion and disengagement. Socio-demographic data were assessed. Results Among 83 participating nurses, we found a prevalence of high disengagement in 17 oncology nurses (20.48%) and high exhaustion (MExh>2.5 = burnout) in 44 (53.00%). Looking at the highest values of both scales, 18.08% of respondents were at high risk for psychological distress. There was a low correlation between disengagement and age (r = 0.331, p < 0.01). The risk of high disengagement among nurses older than 50 (n = 9, 52.94%) was three times higher than for those who were 50 or younger (n = 8, 47.06%) (RR = 8.642, 95% CI: 1.475-5.749, p < 0,01). Conclusion This survey highlights a high rate of burnout among German oncology nurses. Interventions should be developed, implemented, and delivered in an age-appropriate manner. To ensure high-quality care and patient safety, oncology nurses should be offered preventive mental healthcare services later in their careers. Clinical trial registration number The study was registered with the German Clinical Trials Register (DRKS500018851).